Transcutaneous electrical nerve stimulation (TENS) for treatment of constipation in children - Lee, W.S.; Ng, R.T.; Lai, N.M.; Ang, H.L.; Teo, K.M. (JohnWiley & Sons, Ltd., 2013)
The primary objective is to assess the efficacy and safety of TENS used for the treatment of childhood constipation.